Biofeedback in patients with ileoanal pouch dysfunction: a specialist centre experience. (3rd June 2018) - Segal, Jonathan P.; Chan, Heyson; Collins, Brigitte; Faiz, Omar D.; Clark, Susan K.; Hart, Ailsa L.
Abstract: Objectives: To report outcomes following biofeedback for functional problems associated with an ileoanal pouch. Incontinence and evacuatory disorders associated with the ileoanal pouch can be particularly problematic and difficult to treat using conventional therapies. Biofeedback therapy is a behavioural treatment that offers a non-surgical approach as an alternative or adjunct for patients. Materials and methods: This was a retrospective single centre study. We reviewed the notes of all patients attending for biofeedback at our institution between January 2012 and October 2017 and identified all those that did so for ileoanal pouch related problems. We recorded patient reported subjective improvements following biofeedback. The validated International Consultation on Incontinence Questionnaire was used to assess improvement in incontinent symptoms and the evacuatory disorder questionnaire was used to assess improvement in evacuatory disorders. Results: Twenty-six patients with ileoanal pouch related problems underwent biofeedback. Based on patients' feedback at next clinical encounter following biofeedback, nine reported much improvement, 11 reported some improvement and six reported no improvement. In the group treated for incontinence, quality of life improved significantly from a median pre-treatment score of 80 to a post-treatment score of 41 ( p = .01). Biofeedback reduced pain, bloating straining and laxative use in patients with evacuatory disorders. Conclusions: Biofeedback may be associated with significant improvement in quality of life as well as possible improvements in symptoms related to both incontinence and evacuatory disorders. It is probably an underused service. Further larger prospective studies are required to properly assess the efficacy of biofeedback in ileoanal pouch related dysfunction.